The Hadith of the Believers: One Building That Strengthens Each Other: Partial and Simultaneous Analysis of the History of Abu Musa Al Asy'ari in Sahih Al-Bukhari - Nunung Witono; Damanhuri (al-Afkar, Journal For Islamic Studies, 2024)
The aim of this research is to carry out partial and simultaneous analysis of the hadiths of believers in one building which mutually reinforce each other. The scope of this research is the main hadith of the History of Abu Musa Al Asy'ari in Sahih Al-Bukhari. Data relating to hadiths and the quality of each narrator is collected using documentation methods. Data analysis uses the content analysis method. Based on partial analysis, it is found that this hadith has the quality of sahih lidzatih, (1) because all the narrators in the hadith sanad, numbering: five narrators, all have the quality: tsiqah (2) All the narrators each meet with a narrator who has the status of their teacher, thus the sanad muttasil. (3) The matan hadith is apparently not shadh, because it does not conflict with the dalil naqli, both the Qur'an and the hadith whose sanad quality is higher. (4) The matan hadith is also not subject to illat, because it does not conflict with the dalil aqli , whether with common sense, senses, history, or science.